Does Debt Maturity Matter for Investment Decisions? - Chang Woon Nam; Doina Maria Radulescu (Center for Economic Studies and ifo Institute (CESifo), 2004)
In the conventional literature related to investment decisions, less attention has been paid to the length of maturity when investment is debt-financed. In such a case a firm pays the creditor not only the sum of annual interest (initial investment cost multiplied by real interest rate) for the entire borrowing years but also the total amount of initial investment cost at the end of the borrowing period. In this study, the effects of selecting different maturity years on firms' investment decisions are compared on the basis of the simple net present value (NPV) model. Without taxation, the NPV is equal to the present value (PV) of future gross return less the PV of the cost of investment. An investment project is considered to be profitable when the NPV is positive. After the introduction of a corporate income tax, the PV of an asset amounts to the sum of PVs of net return (gross return less taxes) and tax savings led by an incentive depreciation provision. If the investment is debt-financed, the interest payment additionally reduces the corporate tax base. The research findings suggest that (1) ceteris paribus an optimum maturity year appears to exist that maximises the NVP, and (2) the change of optimum debt maturity tends to correlate positively with the corporate tax rate but negatively with the interest rate. In the case of prevailing inflation, there is a mismatch between the nominal interest rate that is a discounting factor for all observed in- and outflows and the real interest rate by which the annual interest payment is determined for the entire maturity period.
Keywords: 330; debt maturity; investment decision; net present value; corporate taxation; inflation